Liberia adherence and loss-to-follow-up in HIV and AIDS care and treatment: A retrospective cohort of adolescents and adults from 2016-2019. - Keith L Gray; Murphy Kiazolu; Janjay Jones; Anna Konstantinova; Jethro S W Zawolo; Wahdae-Mai Harmon Gray; Naomi F Walker; Julia T Garbo; Samretta Caldwell; Michael Odo; Nahid Bhadelia; Jean DeMarco; et al. (Public Library of Science (PLoS), 2022)
Antiretroviral therapy (ART) is a lifesaving intervention for people living with HIV infection, reducing morbidity and mortality; it is likewise essential to reducing transmission. The "Treat all" strategy recommended by the World Health Organization has dramatically increased ART eligibility and improved access. However, retaining patients on ART has been a major challenge for many national programs in low- and middle-income settings, despite actionable local policies and ambitious targets. To estimate retention of patients along the HIV care cascade in Liberia, and identify factors associated with loss-to-follow-up (LTFU), death, and suboptimal treatment adherence, we conducted a nationwide retrospective cohort study utilizing facility and patient-level records. Patients aged ≥15 years, from 28 facilities who were first registered in HIV care from January 2016 -December 2017 were included. We used Cox proportional hazard models to explore associations between demographic and clinical factors and the outcomes of LTFU and death, and a multinomial logistic regression model to investigate factors associated with suboptimal treatment adherence. Among the 4185 records assessed, 27.4% (n = 1145) were males and the median age of the cohort was 37 (IQR: 30-45) years. At 24 months of follow-up, 41.8% (n = 1751) of patients were LTFU, 6.6% (n = 278) died, 0.5% (n = 21) stopped treatment, 3% (n = 127) transferred to another facility and 47.9% (n = 2008) were retained in care and treatment. The incidence of LTFU was 46.0 (95% CI: 40.8-51.6) per 100 person-years. Relative to patients at WHO clinical stage I at first treatment visit, patients at WHO clinical stage III [adjusted hazard ratio (aHR) 1.59, 95%CI: 1.21-2.09; p <0.001] or IV (aHR 2.41, 95%CI: 1.51-3.84; p <0.001) had increased risk of LTFU; whereas at registration, age category 35-44 (aHR 0.65, 95%CI: 0.44-0.98, p = 0.038) and 45 years and older (aHR 0.60, 95%CI: 0.39-0.93, p = 0.021) had a decreased risk. For death, patients assessed with WHO clinical stage II (aHR 2.35, 95%CI: 1.53-3.61, p<0.001), III (aHR 2.55, 95%CI: 1.75-3.71, p<0.001), and IV (aHR 4.21, 95%CI: 2.57-6.89, p<0.001) had an increased risk, while non-pregnant females (aHR 0.68, 95%CI: 0.51-0.92, p = 0.011) and pregnant females (aHR 0.42, 95%CI: 0.20-0.90, p = 0.026) had a decreased risk when compared to males. Suboptimal adherence was strongly associated with the experience of drug side effects-average adherence [adjusted odds ratio (aOR) 1.45, 95% CI: 1.06-1.99, p = 0.02) and poor adherence (aOR 1.75, 95%CI: 1.11-2.76, p = 0.016), and attending rural facility decreased the odds of average adherence (aOR 0.01, 95%CI: 0.01-0.03, p<0.001) and poor adherence (aOR 0.001, 95%CI: 0.0004-0.003, p<0.001). Loss-to-follow-up and poor adherence remain major challenges to achieving viral suppression targets in Liberia. Over two-fifths of patients engaged with the national HIV program are being lost to follow-up within 2 years of beginning care and treatment. WHO clinical stage III and IV were associated with LTFU while WHO clinical stage II, III and IV were associated with death. Suboptimal adherence was further associated with experience of drug side effects. Active support and close monitoring of patients who have signs of clinical progression and/or drug side effects could improve patient outcomes.